Histone Deacetylase Inhibitor Improves the Dysfunction of Hippocampal Gamma Oscillations and Fast Spiking Interneurons in Alzheimer’s Disease Model Mice - Takasu, Keiko; Niidome, Kazuki; Hasegawa, Minoru; Ogawa, Koichi (Frontiers in Molecular Neuroscience, 2021)
The hippocampal gamma oscillation is important for cognitive function, and its deficit is related to cognitive impairment in Alzheimer’s disease (AD). Recently, it has been recognized that post-translational modification via histone acetylation is a fundamental molecular mechanism for regulating synaptic plasticity and cognitive function. However, little is known regarding the regulation of hippocampal gamma oscillation by histone acetylation. We investigated whether histone acetylation regulated kainate-induced gamma oscillations and their important regulator, fast-spiking interneurons, using acute hippocampal slices of AD model mice (PSAPP transgenic mice). We found a decrease in kainate-induced gamma oscillations in slices from PSAPP mice, accompanied with the increased activity of fast spiking interneurons in basal state and the decreased activity in activated state. The histone deacetylase (HDAC) inhibitor (SAHA, named vorinostat) restored deficits of gamma oscillation in PSAPP mice, accompanied with rescue of activity of fast spiking interneurons in basal and activated state. The effect of SAHA was different from that of the clinical AD drug donepezil, which rescued only function of fast spiking interneurons in basal state. Besides, activator of nuclear receptor family 4a (NR4a) receptor (cytosporone B), as one of the epigenetic modification related to HDAC inhibition, rescued the deficits in gamma oscillations in PSAPP mice. These results suggested a novel mechanism in which HDAC inhibition improved impairment of gamma oscillations in PSAPP mice by restoring the activity of fast spiking interneurons both in basal and activated state. The reversal of gamma oscillation deficits by HDAC inhibition and/or NR4a activation appears to be a potential therapeutic target for treating cognitive impairment in AD patients.